Bacterial Tubulins a and B Exhibit Polarized Growth, Mixed-Polarity Bundling, and Destabilization by Gtp Hydrolysis - (:unkn) unknown (American Society for Microbiology, 2017)
Bacteria of the genus Prosthecobacter express homologs of eukaryotic alpha- and beta-tubulin, called BtubA and BtubB (BtubA/B), that have been observed to assemble into filaments in the presence of GTP. BtubA/B polymers are proposed to be composed in vitro by two to six protofilaments in contrast to that in vivo, where they have been reported to form 5-protofilament tubes named bacterial microtubules (bMTs). The btubAB genes likely entered the Prosthecobacter lineage via horizontal gene transfer and may be derived from an early ancestor of the modern eukaryotic microtubule (MT). Previous biochemical studies revealed that BtubA/B polymerization is reversible and that BtubA/B folding does not require chaperones. To better understand BtubA/B filament behavior and gain insight into the evolution of microtubule dynamics, we characterized in vitro BtubA/B assembly using a combination of polymerization kinetics assays and microscopy. Like eukaryotic microtubules, BtubA/B filaments exhibit polarized growth with different assembly rates at each end. GTP hydrolysis stimulated by BtubA/B polymerization drives a stochastic mechanism of filament disassembly that occurs via polymer breakage and/or fast continuous depolymerization. We also observed treadmilling (continuous addition and loss of subunits at opposite ends) of BtubA/B filament fragments. Unlike MTs, polymerization of BtubA/B requires KCl, which reduces the critical concentration for BtubA/B assembly and induces it to form stable mixed-orientation bundles in the absence of any additional BtubA/B-binding proteins. The complex dynamics that we observe in stabilized and unstabilized BtubA/B filaments may reflect common properties of an ancestral eukaryotic tubulin polymer. IMPORTANCE Microtubules are polymers within all eukaryotic cells that perform critical functions; they segregate chromosomes, organize intracellular transport, and support the flagella. These functions rely on the remarkable range of tunable dynamic behaviors of microtubules. Bacterial tubulin A and B (BtubA/B) are evolutionarily related proteins that form polymers. They are proposed to be evolved from the ancestral eukaryotic tubulin, a missing link in microtubule evolution. Using microscopy and biochemical approaches to characterize BtubA/B assembly in vitro, we observed that they exhibit complex and structurally polarized dynamic behavior like eukaryotic microtubules but differ in how they self-associate into bundles and how this bundling affects their stability. Our results demonstrate the diversity of mechanisms through which tubulin homologs promote filament dynamics and monomer turnover.